Combined Pharmacological And Evidence-Based Nursing Interventions For The Management Of Chronic Diabetic Foot Ulcers: A Systematic Review And Network Meta-Analysis (The Review of Diabetic Studies, 2024)
Chronic diabetic foot ulcers (DFUs) are refractory wounds associated with high rates of infection, amputation, and economic burden. While various pharmacological agents and evidence-based nursing procedures exist, the comparative efficacy of their combined clinical application remains unestablished. This study aimed to perform a systematic review and network meta-analysis (NMA) to rank combined pharmacological and nursing-led interventions for chronic DFU management. MEDLINE, Embase, and The Cochrane Library were systematically searched for randomized controlled trials (RCTs) and comparative cohort studies evaluating combined interventions (pharmacological agents plus advanced nursing protocols). The primary outcome was the rate of complete wound healing. Data synthesis was performed using a random-effects Frequentist NMA with Hartung-Knapp-Sidik-Jonkman (HKSJ) adjustment in R (v4.5.1). Intervention hierarchy was established using P-scores. Certainty of evidence was appraised via the CINeMA (Confidence in Network Meta-Analysis) framework. Sixteen studies (N = 2,126 patients) evaluating 10 distinct combined protocols were included. Network geometry followed a star-shaped configuration anchored by Standard Care. Combined protocols demonstrated significant superiority over standard care; the highest magnitude of effect was observed for Keratinocyte-based sheets combined with specialized nursing (OR 36.68; 95% CI: 1.91–703.75; P-score = 0.941), though with low certainty due to imprecision. High-certainty evidence supported the efficacy of macrophage-regulating ON101-Cream (OR 2.85; 95% CI: 1.68–4.84) and MMP-inhibiting Sucrose-Octasulfate dressings (OR 2.14; 95% CI: 1.26–3.64). Technical nursing procedures, specifically Vacuum-Sealing Drainage (VSD) combined with rhEGF (OR 6.13) and Grafix bioactive matrices (OR 6.04), were top-tier rankers. Global heterogeneity was negligible (I2 = 0%), and meta-regression indicated a trend toward reduced efficacy with increasing patient age. Managing chronic DFUs requires a synergistic bio-technical approach. Combined protocols that integrate macrophage regulation or growth factors with technical nursing interventions (NPWT/VSD) are significantly more effective than traditional moisture-balance nursing alone. Clinical guidelines should prioritize these combined interventions for ulcers failing to respond to initial standard management.